APBN PENDIDIKAN DAN MAHALNYA BIAYA PENDIDIKAN - Ridwan Idris (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
The budget of education which has been promoted for an increase would be a reality. The importance of qualified education has been explicitly expressed in the National Constitution, and an increase of educational budget may positively be associated with the quality of education. The remaining problem is the high cost of education particularly for the bottom and middle economic class. Basically, an increase of educational budget would help the com-munity to get access to low cost education easily. Therefore, there must be a political will by the government and the parliament to wisely allocate the budget. In addition, the community and all other stakeholders of educational institutions should control and direct the budget to the right way to achieve qualified education evenly.